IMPLICATIONS OF THE LISBON TREATY FOR LITHUANIA: QUALIFIED MAJORITY AND EU AGENDA - Maniokas, Klaudijus (Politologija, 2015)
This article focuses on the implications of the Lisbon Treaty on the decision-making process in the EU in general and Lithuania in particular. It argues that a new definition of the qualified majority voting (QMV) is an essential novelty of the Lisbon Treaty, which might change the current consensual character of the decision-making in the EU. It might, in turn, penalize those member states, which have specific preferences in certain policy areas. Extention of the QMV implies increasing preassure for the national policy-making. Benefits of this extention are conditioned by the character of the EU agenda at the national level. Articles offers, therefore, evaluation of the Lithuanian EU agenda in this respect.